Jeg vil ikke i fængsel: om den affektive ledelse af de arbejdsløses selvledelse - Pultz, Sabina (Tidsskrift for Professionsstudier, 2018)
Unemployed people are increasingly governed as sensitive beings as management is not only targeted their ability to be rational and responsive in terms of incentives, but also their ability to feel afraid, their ability to feel ashamed and their ability to feel empowered. Based on an analytic from governmentality studies and integrated with a newer affective dimension, empirical material from from a recent PhD project, ”It is not you, it’s me: governing the unemployed self” , following question is analyzed: “How are young unemployed people governed and how do they govern themselves through their emotions?”.